The Impact of Academic Supervision on Teacher’s Professionalism in Improving Educational Quality - Syukri, M Zen; Viona, Elsa; Utama, Hendri Budi (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2023)
The goal of this study was to determine the impact of academic supervision on teacher professionalism in terms of improving educational quality. This study employs a Literature Study with a qualitative approach, involving a series of activities such as collecting library data, reading and taking notes, and managing research materials. Textbooks, journals, scientific articles, and literature were used as data sources. All writings that support data on academic supervision, teacher competency, and school quality were used as secondary data. The findings of this study suggest that academic supervision and teacher professionalism play a role in educational quality. This paper provides knowledge and data that can be used to improve school quality through academic supervision and teacher’s competence.